From destruction to enhanced greening: Quantifying vegetation cover dynamics in Banda Aceh 20 years after the tsunami - Raja Al-Fath; Shiti Maghfira; Ahmad Jihan Muzaki; Arief Gunawan (Journal of Infrastructure Planning and Engineering, 2025)
The 2004 tsunami disaster caused severe ecological damage in Banda Aceh City, destroying a vast majority of its vegetation cover. This study aims to analyze the spatio-temporal dynamics of post-disaster vegetation recovery over two decades (2004-2024) to identify the stages of ecological succession. Using a remote sensing approach, Landsat satellite imagery from 2004 (pre-tsunami), 2005 (post-tsunami), 2014 (one decade later), and 2024 (two decades later) was analyzed using the Normalized Difference Vegetation Index (NDVI). The NDVI classification results show a drastic change: the non-vegetated area surged from 67.58% in 2004 to 89.01% in 2005, while the dense vegetation class was entirely eliminated. However, a recovery process unfolded over the subsequent two decades. By 2024, the non-vegetated area had drastically shrunk to just 13.11%, while the combined area of moderate and dense vegetation surged to over 45% of the city's total area, surpassing the pre-tsunami condition. This study concludes that Banda Aceh has not only successfully restored its vegetation cover but has also undergone a significant ecosystem maturation phase. These findings provide a robust scientific basis for integrating NDVI analysis as a proactive monitoring instrument into the Banda Aceh City Spatial Plan (RTRW) to support sustainable and disaster-resilient urban development.